2011
DOI: 10.1007/s12013-011-9271-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Intercellular Adhesion in Herpex Simplex Virus Infection by Glycyrrhizin

Abstract: Herpes simplex virus (HSV) is one of the most common viruses infecting humans and animals. Cellular adhesion is increased in HSV and plays a role in pathogenesis of inflammatory response during this viral infection. In our study, we studied a potential role of glycyrrhizin in disrupting cellular adhesion in HSV. We isolated rat cerebral capillary vessel endothelial cells (CCECs) and polymorphonuclear leukocytes (PMN) and evaluated intercellular adhesion between these cells by micropipette aspiration technique.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…Like to antitumor effects, it was observed different antiviral effects between quercetin and isoliquiritigenin [ 11 , 13 , 15 , 26 ]. Consistent with previous studies, our study also observed antiviral effects of quercetin and isoliquiritigenin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like to antitumor effects, it was observed different antiviral effects between quercetin and isoliquiritigenin [ 11 , 13 , 15 , 26 ]. Consistent with previous studies, our study also observed antiviral effects of quercetin and isoliquiritigenin.…”
Section: Discussionmentioning
confidence: 99%
“…Physical binding of GA to cohesion resulted in loss of significant roles of CTCF-Cohesin complex on transcription of KSHV latent transcript unit. Hung et al found that GA perfusion in Herpes simplex virus (HSV) infection greatly decreased adhesion and stress between rat cerebral capillary vessel endothelial cells (CCECs) and polymorphonuclear leukocytes (PMN), suggesting that GA may attenuate inflammatory responses in HSV infection [ 15 ]. Therefore, GA is likely to be a major bioactive compound responsible for protective effects of licorice against viral infections.…”
Section: Introductionmentioning
confidence: 99%
“…Many in vitro experiments have shown that GC inhibits HCV by suppressing the release of infectious particles [57], inhibits HSV by depressing the cellular adhesion [58], inhibits influenza virus by reducing HMGB1 binding to DNA and suppressing interactions between viral macromolecules and host proteins [64], inhibits HIV by preventing the virus from replication [61], and inhibits H5N1 not by interfering with H5N1 replication, but by controling H5N1-induced proinflammatory gene expression [60]. The dispute about whether GC inhibits virus replication still needs further study.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Glycyrrhizin, a triterpene saponine, is a constituent of licorice root. Previous studies have demonstrated that glycyrrhizin has the ability to inhibit the proliferation of many viruses, such as hepatitis B virus (HBV) (Sato et al, 1996), hepatitis C virus (HCV) (Matsumoto et al, 2013), herpes simplex virus (HSV) (Huang et al, 2012), SARS coronavirus (Cinatl et al, 2003), and influenza viruses (Wolkerstorfer et al, 2009). In the present study, we aimed to assess the antiviral activity of glycyrrhizin against PRRSV and further elucidate the exact phase of the viral reproductive cycle that is affected by glycyrrhizin.…”
Section: Introductionmentioning
confidence: 99%